Construction of an inducible cell‐communication system that amplifies Salmonella gene expression in tumor tissue. (17th January 2013) - Dai, Yumei; Toley, Bhushan J.; Swofford, Charles A.; Forbes, Neil S.
Abstract Bacterial therapies have the potential to overcome resistances that cause chemotherapies to fail. When using bacteria to produce anticancer agents in tumors, triggering gene expression is necessary to prevent systemic toxicity. The use of chemical triggers, however, is hampered by poor delivery of inducing molecules, which reduces the number of activated bacteria. To solve this problem, we created a cell‐communication system that enables activated bacteria to induce inactive neighbors. We hypothesized that introducing cell communication into Salmonella would improve direct triggering strategies by increasing protein production, increasing sensitivity to inducer molecules, and enabling expression in tumor tissue. To test these hypotheses we integrated the PBAD promoter into the quorum‐sensing machinery from Vibrio fischeri. The expression of a fluorescent reporter gene was compared to expression from non‐communicating controls. Function in three‐dimensional tissue was tested in a tumor‐on‐a‐chip device. Bacterial communication increased fluorescence 40‐fold and increased sensitivity to inducer molecules more than 10, 000‐fold. The system enabled bacteria to activate neighbors and increased the time‐scale of protein production. Gene expression was controllable and tightly regulated. At the optimal inducing signal, communicating bacteria produced 350 times more protein than non‐communicating bacteria. The cell‐communication system created in this study has uses beyond cancer therapy, including protein manufacturing, bioremediation and biosensing. It would enable amplified induction of gene expression in any environment that limits availability of inducer molecules. Ultimately, because inducible cellular communication enables gene expression in tissue, it will be a critical component of bacterial anticancer therapies. Biotechnol. Bioeng. 2013; 110: 1769–1781. © 2012 Wiley Periodicals, Inc.